Optimizing MSME Governance through Financial Digitalization with Accounting Applications to Support Business Growth - Muslim, Ahmad Bukhori; Widati, Sindik; Wulandari, Dian Sulistyorini; Bastanta, Andreas Riski (Jurnal Pengabdian Pancasila (JPP), 2024)
This community service program aimed to empower MSMEs in Tambun Selatan by introducing digital accounting applications to improve financial governance and business management. The initiative included workshops, hands-on training, mentorship sessions, and follow-up support, with 30 MSME participants actively involved. The results indicated significant progress: 70% of participants adopted digital accounting tools, 95% achieved accuracy in financial record-keeping, and 25% reported improved decision-making based on financial insights. Despite these successes, 15% of participants faced challenges due to technical barriers and limited digital literacy. The program also raised awareness of good governance practices, preparing MSMEs for potential collaborations and financial opportunities. Recommendations include sustained mentoring, expanding the program’s reach, enhancing digital literacy, and integrating advanced financial training. This initiative contributes to fostering sustainable MSME growth and aligns with broader efforts to strengthen the local economy through digital transformation.